The effect of price, taste on people’s purchasing interest in batam street food - Hendri Herman; Ismet Jayadi; Agung Wahyu; Heri Sumantoro; Habibilah Al Naufal (Institute of Computer Science (IOCS), 2022)
This research was conducted to determine the influence of price and taste on people's buying interest in street food in Batam city. The sample in this study was street food enthusiasts in Batam city with a total sample of 100 respondents. from the results of the study, it is known that, price has a significant effect on people's buying interest in street food. Therefore, business actors need to pay more attention to setting prices so as not to lose customers. Likewise with taste, from the results of research taste has a significant influence on people's buying interest in street food. Therefore, in order for people to make purchases and repurchases, business actors need to maintain the taste of the product. From the results of simultaneous tests, it can be seen that the price and taste simultaneously have a significant effect on buying interest